A recurrent PAX6 mutation is associated with aniridia and congenital progressive cataract in a Chinese family - Jin, Chongfei (Molecular Vision, 2012)
PURPOSE: Aniridia is phenotyically and genetically heterogeneous. This study is to summarize the phenotypes and identify the genetic defect responsible for aniridia and congenital progressive cataract in a three generation Chinese family. METHODS: A detailed family history and clinical data from patients were collected by ophthalmologic examination, including visual acuity, slit-lamp examination, tonometer, keratometry, corneal topography, optical coherence tomography, and ultrasonic A/B scan. All exons and flanking intronic sequences of the paired box 6 (PAX6) gene were amplified by polymerase chain reaction (PCR) and screened for mutation by direct DNA sequencing. Structure and function of the mutant PAX6 were analyzed by bioinformatics analysis. RESULTS: All the six patients shared common manifestations of complete aniridia, congenital cataract and thickened cornea, and broad phenotypic variability was observed in nystagmus, ptosis, strabismus, glaucoma, corneal pannus, corneal curvature, corneal vascularization, cataract subtype, ectopia lentis, axial length, and optic disc anomalies. Sequencing of the candidate gene detected a heterozygous c.307C>T transition in the coding region of PAX6, resulting in the substitution of a highly conserved arginine codon for a termination codon (p.R103X). The p.P103X mutation co-segregated with the affected individuals in the family. The change was supposed to cause structural and functional changes based on computational analysis. CONCLUSIONS: We identified a recurrent PAX6 c.307C>T mutation in an aniridia and congenital progressive cataract family, and summarized the variable phenotypes among the patients, which expanded the phenotypic spectrum of aniridia in a different ethnic background.